DECONSTRUCTING BEAUTY STANDARDS: A CRITICAL DISCOURSE ANALYSIS OF SOCIAL MEDIA BEAUTY PRODUCT PROMOTION - Muam, Ahmad; Azahra, Ardania Nur Raihan Rizka; Ishak, Nurhamizah Binti (JLA (Jurnal Lingua Applicata), 2025)
This study investigates how two Indonesian beauty brands, Luxcrime and Wardah, construct and communicate idealized beauty standards through the interaction of linguistic and visual modes in their digital promotion. Using a multimodal discourse analysis (MDA) approach, the research integrates Fairclough’s Critical Discourse Analysis, Martinec and Salway’s image–text relations, and Naomi Wolf’s Beauty Myth to examine how vocabulary, tone, visual composition, and discursive patterns contribute to the normalization of aesthetic ideals. Textual analysis reveals that both brands employ evaluative adjectives, affective tone, and dedicated terminology to portray beauty concept. Luxcrime employs “natural perfection” through intimate, influencer-like language that frames self-improvement as self-care, while Wardah highlights rapid, technologically driven transformation through scientific claims such as biomimetic peptide and RadicareTM Gold Oil. Visual analysis shows that both advertisements use pastel palettes, soft lighting, and polished imagery to reinforce narratives of flawlessness, purity, and youthfulness. At the discursive level, both brands propose postfeminist, neoliberal, and wellness ideologies, presenting empowerment as a consumer choice while subtly reinforcing the inadequacy of natural skin. Lastly, in social practice analysis, these advertisements reproduce Indonesian cultural norms that privilege smooth, radiant skin, while simultaneously embedding global beauty discourses within digital consumer culture. The findings highlight that although Luxcrime and Wardah differ in stylistic strategies, emotional intimacy versus scientific efficiency, they ultimately sustain the same ideological construction of beauty as a moral obligation and commodified identity